Perbandingan Tekanan Darah Pada Pasien Hipertensi Obesitas Dan Non Obesitas di Puskesmas Bukit Hindu Palangka Raya - Abigail, Keshia; Balyas , Abi Bakring; Frethernety, Agnes (Fakultas Kedokteran Universitas Palangka Raya, 2025)
Prevalence of hypertension in obese people is much greater and the relative risk of suffering from hypertension in obese people is 5 times higher than in people of normal weight. Hypertension sufferers at the Puskesmas Bukit Hindu in mid-2023 experienced an increase from previous year, which amounted to 107 to 189 cases. The aim of the study was to measure blood pressure in obese and non-obese hypertensive patients at the Bukit Hindu Health Center. This is a type of analytical descriptive research with a cross sectional approach using quantitative descriptive methods. Population in this study were all hypertension sufferers at Puskesmas Bukit Hindu in January – June 2023 who were selected using the Purposive Sampling technique with a total sample of 85 people. Data collection from the Puskesmas Bukit Hindu Medical Record Register Book. The results of bivariate analysis showed that there was a significant difference in systolic and MAP, but there was no significant difference in diastolic between obese and non-obese hypertensive patients. The conclusion of this study is that there is a significant difference between systolic blood pressure and Mean Arterial Pressure (MAP) in obese and non-obese hypertensive patients, but there is no significant difference between diastolic blood pressure in obese and non-obese hypertensive patients at the Bukit Hindu Health Center.